Algorithmic implementation of calculation of energy consumption and determination of the class of energy efficiency of elevators - А. V. Ded; V. A. Tkachenko (Омский научный вестник)
The article presents the results of the implementation of the developed algorithm for calculating the energy consumption of elevators in order to determine the class of their energy efficiency. The algorithm is based on methods for measuring the actual energy consumption of elevators in use or released into circulation. The practical implementation of the generated calculation algorithm is performed in the Microsoft Visual Studio software environment. The generated program report complies with the requirements of the current regulatory documentation GOST R 56420.2-2015 «Passenger elevators, escalators and conveyors. Energy characteristics».